Finance and Development, June 1971. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1971)
This paper examines the difference between 'capital' and 'investment' for developing countries. The paper highlights that investment in material capital is merely one of the factors involved in economic development and that current expenditures on health, education, agricultural extension, family planning, research, management training, and so on, may be equally important or even more important than investment in capital. The paper offers a brief historical survey, drawing attention to factors leading to the development of a market where savers and investors are brought together.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet